The Limits of Recidivism: Measuring Success After Prison - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
Nearly 600,000 people are released from state and federal prisons annually. Whether these individuals will successfully reintegrate into their communities has been identified as a critical measure of the effectiveness of the criminal legal system. However, evaluating the successful reentry of individuals released from prison is a challenging process, particularly given limitations of currently available data and the complex set of factors that shape reentry experiences. The Limits of Recidivism: Measuring Success After Prison finds that the current measures of success for individuals released from prison are inadequate. The use of recidivism rates to evaluate post-release success ignores significant research on how and why individuals cease to commit crimes, as well as the important role of structural factors in shaping post-release outcomes. The emphasis on recidivism as the primary metric to evaluate post-release success also ignores progress in other domains essential to the success of individuals returning to communities, including education, health, family, and employment. In addition, the report highlights the unique and essential insights held by those who have experienced incarceration and proposes that the development and implementation of new measures of post-release success would significantly benefit from active engagement with individuals with this lived experience. Despite significant challenges, the report outlines numerous opportunities to improve the measurement of success among individuals released from prison and the report2019s recommendations, if implemented, will contribute to policies that increase the health, safety, and security of formerly incarcerated persons and the communities to which they return.

Juvenile Crime, Juvenile Justice - National Research Council; Institute of Medicine
Even though youth crime rates have fallen since the mid-1990s, public fear and political rhetoric over the issue have heightened. The Columbine shootings and other sensational incidents add to the furor. Often overlooked are the underlying problems of child poverty, social disadvantage, and the pitfalls inherent to adolescent decisionmaking that contribute to youth crime. From a policy standpoint, adolescent offenders are caught in the crossfire between nurturance of youth and punishment of criminals, between rehabilitation and \

Health and Incarceration: A Workshop Summary - Institute of Medicine; National Research Council (The National Academies Press, 2013)
Over the past four decades, the rate of incarceration in the United States has skyrocketed to unprecedented heights, both historically and in comparison to that of other developed nations. At far higher rates than the general population, those in or entering U.S. jails and prisons are prone to many health problems. This is a problem not just for them, but also for the communities from which they come and to which, in nearly all cases, they will return. Health and Incarceration is the summary of a workshop jointly sponsored by the National Academy of Sciences(NAS) Committee on Law and Justice and the Institute of Medicine(IOM) Board on Health and Select Populations in December 2012. Academics, practitioners, state officials, and nongovernmental organization representatives from the fields of healthcare, prisoner advocacy, and corrections reviewed what is known about these health issues and what appear to be the best opportunities to improve healthcare for those who are now or will be incarcerated. The workshop was designed as a roundtable with brief presentations from 16 experts and time for group discussion. Health and Incarceration reviews what is known about the health of incarcerated individuals, the healthcare they receive, and effects of incarceration on public health. This report identifies opportunities to improve healthcare for these populations and provides a platform for visions of how the world of incarceration health can be a better place.

Reducing Racial Inequality in Crime and Justice: Science, Practice, and Policy - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
The history of the U.S. criminal justice system is marked by racial inequality and sustained by present day policy. Large racial and ethnic disparities exist across the several stages of criminal legal processing, including in arrests, pre-trial detention, and sentencing and incarceration, among others, with Black, Latino, and Native Americans experiencing worse outcomes. The historical legacy of racial exclusion and structural inequalities form the social context for racial inequalities in crime and criminal justice. Racial inequality can drive disparities in crime, victimization, and system involvement. Reducing Racial Inequality in Crime and Justice: Science, Practice, and Policy synthesizes the evidence on community-based solutions, noncriminal policy interventions, and criminal justice reforms, charting a path toward the reduction of racial inequalities by minimizing harm in ways that also improve community safety. Reversing the effects of structural racism and severing the close connections between racial inequality, criminal harms such as violence, and criminal justice involvement will involve fostering local innovation and evaluation, and coordinating local initiatives with state and federal leadership. This report also highlights the challenge of creating an accurate, national picture of racial inequality in crime and justice: there is a lack of consistent, reliable data, as well as data transparency and accountability. While the available data points toward trends that Black, Latino, and Native American individuals are overrepresented in the criminal justice system and given more severe punishments compared to White individuals, opportunities for improving research should be explored to better inform decision-making.

The Growth of Incarceration in the United States: Exploring Causes and Consequences - National Research Council (The National Academies Press, 2014)
After decades of stability from the 1920s to the early 1970s, the rate of imprisonment in the United States more than quadrupled during the last four decades. The U.S. penal population of 2.2 million adults is by far the largest in the world. Just under one-quarter of the world's prisoners are held in American prisons. The U.S. rate of incarceration, with nearly 1 out of every 100 adults in prison or jail, is 5 to 10 times higher than the rates in Western Europe and other democracies. The U.S. prison population is largely drawn from the most disadvantaged part of the nation's population: mostly men under age 40, disproportionately minority, and poorly educated. Prisoners often carry additional deficits of drug and alcohol addictions, mental and physical illnesses, and lack of work preparation or experience. The growth of incarceration in the United States during four decades has prompted numerous critiques and a growing body of scientific knowledge about what prompted the rise and what its consequences have been for the people imprisoned, their families and communities, and for U.S. society. The Growth of Incarceration in the United States examines research and analysis of the dramatic rise of incarceration rates and its affects. This study makes the case that the United States has gone far past the point where the numbers of people in prison can be justified by social benefits and has reached a level where these high rates of incarceration themselves constitute a source of injustice and social harm. The Growth of Incarceration in the United States recommends changes in sentencing policy, prison policy, and social policy to reduce the nation's reliance on incarceration. The report also identifies important research questions that must be answered to provide a firmer basis for policy. The study assesses the evidence and its implications for public policy to inform an extensive and thoughtful public debate about and reconsideration of policies.

The Effects of Incarceration and Reentry on Community Health and Well-Being: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
The high rate of incarceration in the United States contributes significantly to the nation's health inequities, extending beyond those who are imprisoned to families, communities, and the entire society. Since the 1970s, there has been a seven-fold increase in incarceration. This increase and the effects of the post-incarceration reentry disproportionately affect low-income families and communities of color. It is critical to examine the criminal justice system through a new lens and explore opportunities for meaningful improvements that will promote health equity in the United States. The National Academies convened a workshop on June 6, 2018 to investigate the connection between incarceration and health inequities to better understand the distributive impact of incarceration on low-income families and communities of color. Topics of discussion focused on the experience of incarceration and reentry, mass incarceration as a public health issue, women's health in jails and prisons, the effects of reentry on the individual and the community, and promising practices and models for reentry. The programs and models that are described in this publication are all Philadelphia-based because Philadelphia has one of the highest rates of incarceration of any major American city. This publication summarizes the presentations and discussions of the workshop.

Fairness and Effectiveness in Policing: The Evidence - National Research Council
Because police are the most visible face of government power for most citizens, they are expected to deal effectively with crime and disorder and to be impartial. Producing justice through the fair, and restrained use of their authority. The standards by which the public judges police success have become more exacting and challenging. Fairness and Effectiveness in Policing explores police work in the new century. It replaces myths with research findings and provides recommendations for updated policy and practices to guide it. The book provides answers to the most basic questions: What do police do? It reviews how police work is organized, explores the expanding responsibilities of police, examines the increasing diversity among police employees, and discusses the complex interactions between officers and citizens. It also addresses such topics as community policing, use of force, racial profiling, and evaluates the success of common police techniques, such as focusing on crime \

The Criminal Justice System and Social Exclusion: Race, Ethnicity, and Gender: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
The National Academies of Sciences, Engineering, and Medicine convened a workshop in April 2018 to examine how the criminal justice system affects the fundamental status of people as members of society and to consider next steps for research, practice, and policy for the field. The goal of the workshop was to find common ground to work toward a criminal justice system that avoids social exclusion and instead reflects the principles of citizenship and social justice with a fair distribution of rights, resources and opportunities. The workshop was specifically designed to explore the reasons for the disparate experiences of individuals involved with the criminal justice system by race, ethnicity, and gender, the mechanisms that cause them to persist, and what can be done through policy and practice to minimize those differences. Participants2014including researchers, policy makers, and advocates for victims and offenders2014discussed issues in five areas: (1) the role of criminal justice in social exclusion; (2) patterns of inequality in criminal justice; (3) collateral sanctions of the criminal justice system; (4) special concerns for youth and young adult populations; and (5) next steps for research, policy, and practice. This publication summarizes the presentations and discussions from the workshop.

Reforming Juvenile Justice: A Developmental Approach - National Research Council (The National Academies Press, 2013)
Adolescence is a distinct, yet transient, period of development between childhood and adulthood characterized by increased experimentation and risk-taking, a tendency to discount long-term consequences, and heightened sensitivity to peers and other social influences. A key function of adolescence is developing an integrated sense of self, including individualization, separation from parents, and personal identity. Experimentation and novelty-seeking behavior, such as alcohol and drug use, unsafe sex, and reckless driving, are thought to serve a number of adaptive functions despite their risks. Research indicates that for most youth, the period of risky experimentation does not extend beyond adolescence, ceasing as identity becomes settled with maturity. Much adolescent involvement in criminal activity is part of the normal developmental process of identity formation and most adolescents will mature out of these tendencies. Evidence of significant changes in brain structure and function during adolescence strongly suggests that these cognitive tendencies characteristic of adolescents are associated with biological immaturity of the brain and with an imbalance among developing brain systems. This imbalance model implies dual systems: one involved in cognitive and behavioral control and one involved in socio-emotional processes. Accordingly adolescents lack mature capacity for self-regulations because the brain system that influences pleasure-seeking and emotional reactivity develops more rapidly than the brain system that supports self-control. This knowledge of adolescent development has underscored important differences between adults and adolescents with direct bearing on the design and operation of the justice system, raising doubts about the core assumptions driving the criminalization of juvenile justice policy in the late decades of the 20th century. It was in this context that the Office of Juvenile Justice and Delinquency Prevention (OJJDP) asked the National Research Council to convene a committee to conduct a study of juvenile justice reform. The goal of Reforming Juvenile Justice: A Developmental Approach was to review recent advances in behavioral and neuroscience research and draw out the implications of this knowledge for juvenile justice reform, to assess the new generation of reform activities occurring in the United States, and to assess the performance of OJJDP in carrying out its statutory mission as well as its potential role in supporting scientifically based reform efforts.

Securing the Vote: Protecting American Democracy - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
During the 2016 presidential election, America's election infrastructure was targeted by actors sponsored by the Russian government. Securing the Vote: Protecting American Democracy examines the challenges arising out of the 2016 federal election, assesses current technology and standards for voting, and recommends steps that the federal government, state and local governments, election administrators, and vendors of voting technology should take to improve the security of election infrastructure. In doing so, the report provides a vision of voting that is more secure, accessible, reliable, and verifiable.

Support for Forensic Science Research: Improving the Scientific Role of the National Institute of Justice - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2015)
Reliable and valid forensic science analytic techniques are critical to a credible, fair, and evidence-based criminal justice system. There is widespread agreement that the scientific foundation of some currently available forensic science methods needs strengthening and that additional, more efficient techniques are urgently needed. These needs can only be met through sustained research programs explicitly designed to ensure and improve the reliability and validity of current methods and to foster the development and use of new and better techniques. This task is challenging due to the broad nature of the field. Concerns have been raised repeatedly about the ability of the criminal justice system to collect and analyze evidence efficiently and to be fair in its verdicts. Although significant progress has been made in some forensic science disciplines, the forensic science community still faces many challenges. Federal leadership, particularly in regard to research and the scientific validation of forensic science methods, is needed to help meet the pressing issues facing state and local jurisdictions. This report reviews the progress made by the National Institute of Justice (NIJ) to advance forensic science research since the 2009 report, Strengthening Forensic Science in the United States: A Path Forward and the 2010 report, Strengthening the National Institute of Justice. Support for Forensic Science Research examines the ways in which NIJ develops its forensic science research priorities and communicates those priorities as well as its findings to the scientific and forensic practitioner communities in order to determine the impact of NIJ forensic science research programs and how that impact can be enhanced.

New Directions in Child Abuse and Neglect Research - Institute of Medicine; National Research Council (The National Academies Press, 2014)
Each year, child protective services receive reports of child abuse and neglect involving six million children, and many more go unreported. The long-term human and fiscal consequences of child abuse and neglect are not relegated to the victims themselves2014they also impact their families, future relationships, and society. In 1993, the National Research Council (NRC) issued the report, Under-standing Child Abuse and Neglect, which provided an overview of the research on child abuse and neglect. New Directions in Child Abuse and Neglect Research updates the 1993 report and provides new recommendations to respond to this public health challenge. According to this report, while there has been great progress in child abuse and neglect research, a coordinated, national research infrastructure with high-level federal support needs to be established and implemented immediately. New Directions in Child Abuse and Neglect Research recommends an actionable framework to guide and support future child abuse and neglect research. This report calls for a comprehensive, multidisciplinary approach to child abuse and neglect research that examines factors related to both children and adults across physical, mental, and behavioral health domains2014including those in child welfare, economic support, criminal justice, education, and health care systems2014and assesses the needs of a variety of subpopulations. It should also clarify the causal pathways related to child abuse and neglect and, more importantly, assess efforts to interrupt these pathways. New Directions in Child Abuse and Neglect Research identifies four areas to look to in developing a coordinated research enterprise: a national strategic plan, a national surveillance system, a new generation of researchers, and changes in the federal and state programmatic and policy response.

Identifying the Culprit: Assessing Eyewitness Identification - National Research Council (The National Academies Press, 2014)
Identifying the Culprit: Assessing Eyewitness Identification makes the case that better data collection and research on eyewitness identification, new law enforcement training protocols, standardized procedures for administering line-ups, and improvements in the handling of eyewitness identification in court can increase the chances that accurate identifications are made. This report explains the science that has emerged during the past 30 years on eyewitness identifications and identifies best practices in eyewitness procedures for the law enforcement community and in the presentation of eyewitness evidence in the courtroom. In order to continue the advancement of eyewitness identification research, the report recommends a focused research agenda.

Confronting Commercial Sexual Exploitation and Sex Trafficking of Minors in the United States - Institute of Medicine; National Research Council (The National Academies Press, 2013)
Every day in the United States, children and adolescents are victims of commercial sexual exploitation and sex trafficking. Despite the serious and long-term consequences for victims as well as their families, communities, and society, efforts to prevent, identify, and respond to these crimes are largely under supported, inefficient, uncoordinated, and unevaluated. Confronting Commercial Sexual Exploitation and Sex Trafficking of Minors in the United States examines commercial sexual exploitation and sex trafficking of U.S. citizens and lawful permanent residents of the United States under age 18. According to this report, efforts to prevent, identify, and respond to these crimes require better collaborative approaches that build upon the capabilities of people and entities from a range of sectors. In addition, such efforts need to confront demand and the individuals who commit and benefit from these crimes. The report recommends increased awareness and understanding, strengthening of the law's response, strengthening of research to advance understanding and to support the development of prevention and intervention strategies, support for multi-sector and interagency collaboration, and creation of a digital information-sharing platform. A nation that is unaware of these problems or disengaged from solutions unwittingly contributes to the ongoing abuse of minors. If acted upon in a coordinated and comprehensive manner, the recommendations of Confronting Commercial Sexual Exploitation and Sex Trafficking of Minors in the United States can help advance and strengthen the nation's emerging efforts to prevent, identify, and respond to commercial sexual exploitation and sex trafficking of minors in the United States.

Facial Recognition Technology: Current Capabilities, Future Prospects, and Governance - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2024)
Facial recognition technology is increasingly used for identity verification and identification, from aiding law enforcement investigations to identifying potential security threats at large venues. However, advances in this technology have outpaced laws and regulations, raising significant concerns related to equity, privacy, and civil liberties. This report explores the current capabilities, future possibilities, and necessary governance for facial recognition technology. Facial Recognition Technology discusses legal, societal, and ethical implications of the technology, and recommends ways that federal agencies and others developing and deploying the technology can mitigate potential harms and enact more comprehensive safeguards.

Reference Manual on Scientific Evidence: Third Edition - National Research Council (The National Academies Press, 2011)
The Reference Manual on Scientific Evidence, Third Edition, assists judges in managing cases involving complex scientific and technical evidence by describing the basic tenets of key scientific fields from which legal evidence is typically derived and by providing examples of cases in which that evidence has been used. First published in 1994 by the Federal Judicial Center, the Reference Manual on Scientific Evidence has been relied upon in the legal and academic communities and is often cited by various courts and others. Judges faced with disputes over the admissibility of scientific and technical evidence refer to the manual to help them better understand and evaluate the relevance, reliability and usefulness of the evidence being proffered. The manual is not intended to tell judges what is good science and what is not. Instead, it serves to help judges identify issues on which experts are likely to differ and to guide the inquiry of the court in seeking an informed resolution of the conflict. The core of the manual consists of a series of chapters (reference guides) on various scientific topics, each authored by an expert in that field. The topics have been chosen by an oversight committee because of their complexity and frequency in litigation. Each chapter is intended to provide a general overview of the topic in lay terms, identifying issues that will be useful to judges and others in the legal profession. They are written for a non-technical audience and are not intended as exhaustive presentations of the topic. Rather, the chapters seek to provide judges with the basic information in an area of science, to allow them to have an informed conversation with the experts and attorneys.

The Polygraph and Lie Detection - National Research Council (The National Academies Press, 2003)
The polygraph, often portrayed as a magic mind-reading machine, is still controversial among experts, who continue heated debates about its validity as a lie-detecting device. As the nation takes a fresh look at ways to enhance its security, can the polygraph be considered a useful tool? The Polygraph and Lie Detection puts the polygraph itself to the test, reviewing and analyzing data about its use in criminal investigation, employment screening, and counter-intelligence. The book looks at: The theory of how the polygraph works and evidence about how deceptiveness2014and other psychological conditions2014affect the physiological responses that the polygraph measures. Empirical evidence on the performance of the polygraph and the success of subjects' countermeasures. The actual use of the polygraph in the arena of national security, including its role in deterring threats to security. The book addresses the difficulties of measuring polygraph accuracy, the usefulness of the technique for aiding interrogation and for deterrence, and includes potential alternatives2014such as voice-stress analysis and brain measurement techniques.